The Best Model of Economic Governance in Managing Old Well - Noto Pamungkas; Sri Suryaningsum (Jurnal Manajemen Dayasaing, 2018)
This research is to analyzethe management of oil and gas old well in Wonocolo. Bojonegoro is really unique and interesting to be observed. The latest plan is that this area will be purposed into sustainable development to protect the environment in its surrounding, more over, this area is aimed to be a tourism object. The researchers hope that the result of this research gives significant contribution, especially in terms of good economic governance, for management of old oil and gas in Wonocolo if the minersswitched tothe tourism sector.The activity of traditional mining in this area cannot be strained from by year. The negative effects which appear are damaged environment, mining activity legality, unstrained pollution, insecurely working, and other social problems. Based on this thoughtfulness, the government of Bojonegoro endeavours the idea of enlightening the traditional miner, exploiting it to be educational system of oil and gas management (educational tourism). This activity needs to be socialized well, to change the habit of traditional miners to be tourism agent. The aim of this research is to give idea or contribution to rearrange the oil and gas old well that has been already exist, especially the object of this research is in Wonocolo, Bojonegoro. Oil and gas old well mining is not merely to process oil and gas mining, but more than that, the existence of it can support the economic condition of local citizens and also repair the infrastructure independently. Because of this, the local income and prosperity of local people will be increase, and the poverty will be decrease.Keywords: oil and gas tourism, local economy, traditional mining of oil and gas old well in Wonocolo, Bojonegoro.